2022
DOI: 10.1101/2022.07.01.22277111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycolysis-enhancing α1-adrenergic antagonists modify cognitive symptoms related to Parkinson’s disease

Abstract: Terazosin is an α1-adrenergic receptor antagonist that enhances glycolysis and increases cellular ATP by binding to the enzyme phosphoglycerate kinase 1 (PGK1). Recent work has shown that terazosin is protective against motor dysfunction in rodent models of Parkinson's disease (PD) and is associated with slowed motor symptom progression in PD patients. However, PD is also characterized by profound cognitive symptoms. We tested the hypothesis that terazosin protects against cognitive symptoms associated with PD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…We also quantified tyrosine hydroxylase positive (TH+) fluorescence levels in the PFC, striatum, ventral tegmental area, and substantia nigra (Fig. 2G), similar to prior methods established in the lab (Weber et al, 2022). We found no significant change in TH+ fluorescent levels in PFF-injected mice compared with controls in any of the four regions: PFC ( t (14) = 0.38; p = 0.71), striatum ( t (14) = 0.07; p = 0.99), ventral tegmental area ( t (14) = 0.57; p = 0.58), and substantia nigra ( t (14) = 0.10; p = 0.92).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also quantified tyrosine hydroxylase positive (TH+) fluorescence levels in the PFC, striatum, ventral tegmental area, and substantia nigra (Fig. 2G), similar to prior methods established in the lab (Weber et al, 2022). We found no significant change in TH+ fluorescent levels in PFF-injected mice compared with controls in any of the four regions: PFC ( t (14) = 0.38; p = 0.71), striatum ( t (14) = 0.07; p = 0.99), ventral tegmental area ( t (14) = 0.57; p = 0.58), and substantia nigra ( t (14) = 0.10; p = 0.92).…”
Section: Resultsmentioning
confidence: 99%
“…The data presented here, and our prior report demonstrate that PFC PFFs are not sufficient to affect interval timing. This may because midbrain dopaminergic cell loss, which is absent in this model, may be necessary for interval timing deficits (Kim et al, 2017; Weber et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that impaired energy metabolism is a critical factor in PD, and preclinical studies have found that terazosin, a glycolysis‐enhancing agent, increases energy metabolism and protects against motor degeneration in the MPTP mouse model, 6‐OHDA rat model, and synuclein‐overexpressing mice 38 . The analysis of the human PD patient database suggests that terazosin is associated with slowed motor symptom progression and even protection against developing PD 38,39 . Interestingly, PGK1 's chromosomic location, Xq21.1, lies inside the susceptibility locus for classical PD associated with PARK12, Xq21‐q25, which has no identified gene yet 35 …”
Section: Discussionmentioning
confidence: 99%